Experimental Study on Drilling Signal Characteristics of PDC Drill Bit in Media of Different Strengths and Identification of Weak Media - Zheng Wu; Yingbo Fan; Huazhou Chen (Sensors)
This study aimed to investigate the drilling signal characteristics when a PDC drill bit penetrates media of different strengths and to assess the potential of these signals for identifying weak layers within rock formations. Laboratory-scale experiments were conducted, and the response characteristics of the PDC drill bit in different-strength media were analyzed across the time domain, frequency domain, and time–frequency domain using statistical analysis, Fourier transform, and empirical mode decomposition (EMD). The results indicate that in the lowest-strength concrete (C10), the drilling speed was the fastest, while the mean, median, and primary distribution ranges of the thrust and torque were the smallest. Some dimensionless time-domain and frequency-domain indicators were found to have limitations in differentiating media of varying strengths. Meanwhile, the time–frequency analysis and EMD of the thrust and torque signals revealed distinct changes at the media boundaries, serving as auxiliary criteria for identifying transitions between different media. The time–frequency analysis and EMD demonstrated clear advantages in identifying these boundaries. These findings provide a theoretical basis for using drilling signals to identify weak layers that pose potential roof collapse hazards in roadway roof strata.